1985
DOI: 10.1093/brain/108.3.697
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of Premotor Cortex in Man

Abstract: Moderate unilateral weakness of shoulder and hip muscles and limb-kinetic apraxia were observed in 11 patients with frontal lobe lesions on the side opposite to the neurological deficits. On the CT scans, the posterior border of the lesions lay anterior to the precentral gyrus, thus involving the premotor cortex but not the primary motor cortex. In 9 cases, the lesions were caused by a brain infarct, in 2 cases by a tumour. In 1 patient the lesion was purely subcortical. Whereas the paresis affected all hip mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(84 citation statements)
references
References 68 publications
5
74
0
5
Order By: Relevance
“…Theoretical formulations have ascribed to the PMA a central role in the maintenance of ''motor set.'' Lesions in this area impair motor control (29). The effect seen in the medial wall, comprising the posterior (behind the anterior commissure) SMA and a locus in the cingulate gyrus bilaterally, again is in accordance with results of previous nonparametric neuroimaging studies (24,30,31).…”
Section: Discussionsupporting
confidence: 89%
“…Theoretical formulations have ascribed to the PMA a central role in the maintenance of ''motor set.'' Lesions in this area impair motor control (29). The effect seen in the medial wall, comprising the posterior (behind the anterior commissure) SMA and a locus in the cingulate gyrus bilaterally, again is in accordance with results of previous nonparametric neuroimaging studies (24,30,31).…”
Section: Discussionsupporting
confidence: 89%
“…The chronological coordination of motor cortical activity in performing voluntary movements is controlled by areas of the secondary motor cortex. Changes in the activation sequence of arm muscles in damage to the premotor cortex have already been observed (Freund and Hummelsheim, 1985). arm was rotated to ventral in flexion movement, it was parallel to the axis of the body in abduction.…”
Section: Methodsmentioning
confidence: 89%
“…Bütefisch et al [39] reported that repetition of a specific movement is a critical component of motor recovery in stroke patients. Repetitive training influences the functional recovery of synaptic plasticity, which includes alternative descending pathway, secondary motor area, and ipsilateral motor area [40][41][42][43][44]. Page et al [45] recently reported that sufficient task-related training with electrical stimulation can elicit the largest and most consistent upper limb motor changes in stroke patients, compared to a lowfrequency exercise group or a sham group.…”
Section: Discussionmentioning
confidence: 99%